Competition and the role of group identity - Francesca Cornaglia; Michalis Drouvelis; Paolo Masella (Center for Economic Studies and ifo Institute (CESifo), 2019)
The emergence of competition is a defining aspect of human nature and characterizes many important social environments. However, its relationship with how social groups are formed has received little attention. We design an experiment to analyze how individuals' willingness to compete is affected by group identity. We find that individuals display substantially stronger competitiveness in within group (ingroup) matchings than in between group (outgroup) matchings or in a control setting where no group identity is induced. We also find that the effect of group identity is stronger for subjects who participated more actively in the team-building task.
Keywords: C92; D03; 330; competition; social distance; group identity; laboratory experiment